2015
DOI: 10.1063/1.4928078
|View full text |Cite
|
Sign up to set email alerts
|

Like-charged protein-polyelectrolyte complexation driven by charge patches

Abstract: We study the pair complexation of a single, highly charged polyelectrolyte (PE) chain (of 25 or 50 monomers) with like-charged patchy protein models (CPPMs) by means of implicit-solvent, explicit-salt Langevin dynamics computer simulations. Our previously introduced set of CPPMs embraces well-defined zero-, one-, and two-patched spherical globules each of the same net charge and (nanometer) size with mono- and multipole moments comparable to those of globular proteins with similar size. We observe large bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
86
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(88 citation statements)
references
References 66 publications
2
86
0
Order By: Relevance
“…We finally note that the discontinuity observed in the PE-PE association process may also emerge during the complexation of PEs and globular proteins as indicated in recent coarse-grained computer simulations of more [39] or less [38] resolved protein models with heterogeneous charge distributions. In these cases, counterion-release effects after PE binding to protein surface charge patches have also been identified as the main non-specific interaction responsible for the PE-protein complexation.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
See 2 more Smart Citations
“…We finally note that the discontinuity observed in the PE-PE association process may also emerge during the complexation of PEs and globular proteins as indicated in recent coarse-grained computer simulations of more [39] or less [38] resolved protein models with heterogeneous charge distributions. In these cases, counterion-release effects after PE binding to protein surface charge patches have also been identified as the main non-specific interaction responsible for the PE-protein complexation.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%
“…Similar values of r 0 can be estimated from an inspection of the radial distribution of counterions (not shown) around the PE beads (see, e.g., Refs. [38,39,53]). …”
Section: B Charge Densities and Counterion Condensationmentioning
confidence: 99%
See 1 more Smart Citation
“…As pointed out in Section 2.1, this class of proteins is related to charged patchy colloids, and several models are being developed in this respect. 100,103 The appropriate modeling of directional interactions caused by charge inhomogeneities can be challenging, in particular with respect to specific ion effects: for instance, by forming salt bridges, multivalent ions have very drastic effects on the effective interactions between proteins in solution to the point of rendering directional charge repulsions attractive. 116 More refined models which take into account electric multipoles as well as the distribution of charged, neutral and hydrophobic residues have been developed.…”
Section: Patchy Proteinsmentioning
confidence: 99%
“…97 A different modeling of charged Janus colloids was proposed to investigate the relation between the order of the multipolar expansion of the inter-particle potential and the resulting minimum-energy clusters. 98 In the context of globular proteins, a set of charged patchy particle models was introduced 99 to study the adsorption of such units on a polyelectrolyte chain 100 or on a polyelectrolyte brush layer. 101 These charged patchy models 99 have also been used to investigate the effect of multivalent electrolytes on the orientational correlations between the patchy units: it was shown that a careful choice of electrolytes could be used to steer the particle assembly.…”
Section: Charged Patchy Colloidsmentioning
confidence: 99%